Rhodium(III)‐Catalyzed Oxidative C(sp3)−H Alkenylation of 8‐Methylquinolines with Maleimides Under Aerobic Conditions. Issue 12 (17th April 2020) - Shan, Baode; Kang, Baotao; Song, Mingyue; Wang, Rui; Chen, Guozhu; Li, Cuncheng; Zhao, Huaiqing
Abstract: A rhodium(III)‐catalyzed C(sp 3 )−H alkenylation of 8‐methylquinolines with electron‐deficient maleimides has been accomplished with the combination of copper acetate, 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl and oxygen as the oxidant. A variety of maleimides react with various 8‐methylquinolines to furnish the corresponding alkenylated products in moderate to good yields. Abstract :